2023
DOI: 10.1136/ard-2023-224250
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatology and Long COVID: lessons from the study of fibromyalgia

Abstract: Rheumatology, such as other subspecialties, has both a unique perspective to offer as well as an evolving role to play in the global COVID-19 pandemic. Our field has already contributed meaningfully to the development and repurposing of many of the immune-based therapeutics which are now standard treatments for severe forms of the disease as well as to the understanding of the epidemiology, risk factors and natural history of COVID-19 in immune-mediated inflammatory diseases. Still in evolution is our potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Cluster 1 encompasses a significantly higher number of patients suffering from FM in comparison to Cluster 2 (PV < 0.001 for SSS and PV = 0.053 for WPI): 25 (43.1%) vs. 12 (21.4%), respectively, with a high rate (32.7% vs. 16%, respectively) of new diagnosis appearing simultaneously surrounding developing Long COVID syndrome. This observation strengthens the connection between Long COVID and FM, which is the focus of extensive research, indicating shared pathophysiology, risk factors, and similar manifestations [47].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Cluster 1 encompasses a significantly higher number of patients suffering from FM in comparison to Cluster 2 (PV < 0.001 for SSS and PV = 0.053 for WPI): 25 (43.1%) vs. 12 (21.4%), respectively, with a high rate (32.7% vs. 16%, respectively) of new diagnosis appearing simultaneously surrounding developing Long COVID syndrome. This observation strengthens the connection between Long COVID and FM, which is the focus of extensive research, indicating shared pathophysiology, risk factors, and similar manifestations [47].…”
Section: Discussionsupporting
confidence: 80%
“…The clinical and possible pathogenetic overlap between Long COVID and FM is an evolving concept that has attracted significant interest in the current literature [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…This dysfunction leads to abnormal production of reactive oxygen species (ROS) with possible induction of chronic pain [ 146 , 147 ]. In summary, it can be speculated that the close relationship between long COVID and FM may be an important clue to clarify aspects of FM [ 148 ].…”
Section: The Role Of Pathogensmentioning
confidence: 99%
“…A subset of patients with FM had elevated levels of anti-satellite glial cell antibodies, but this was not associated with cytokine release or with systemic inflammation (61). It has been suggested that the nociplastic pain characteristic of FM, ME/CFS, and long COVID may share similar glial brain activation pathways (62,63).…”
Section: Similar Pathophysiologic Pathways (Table 3)mentioning
confidence: 99%